2009
DOI: 10.1093/aob/mcp151
|View full text |Cite
|
Sign up to set email alerts
|

Response to non-uniform salinity in the root zone of the halophyte Atriplex nummularia: growth, photosynthesis, water relations and tissue ion concentrations

Abstract: Atriplex nummularia with one root half in 10 mm NaCl maintained net photosynthesis, shoot growth and shoot water potential even when the other root half was exposed to 670 mm NaCl, a concentration that inhibits growth by 65 % when uniform in the root zone. Given the likelihood of non-uniform salinity in many field situations, this situation would presumably benefit halophyte growth and physiology in saline environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 31 publications
9
52
0
Order By: Relevance
“…In cotton growing in a split-root experiment, plant biomass was determined by the lowest salinity in the root zone (Dong et al 2010), supporting hypothesis #2. However, growth and photosynthesis of the halophyte Artiplex nummularia was determined by the mean salinity of the root zone (Bazihizina et al 2009), supporting hypothesis #3.…”
Section: Introductionmentioning
confidence: 61%
“…In cotton growing in a split-root experiment, plant biomass was determined by the lowest salinity in the root zone (Dong et al 2010), supporting hypothesis #2. However, growth and photosynthesis of the halophyte Artiplex nummularia was determined by the mean salinity of the root zone (Bazihizina et al 2009), supporting hypothesis #3.…”
Section: Introductionmentioning
confidence: 61%
“…Given this progress, the stage is now certainly set to use similar techniques to advance our understanding of responses to salinity and their effects on other processes (Bazihizina et al 2009(Bazihizina et al , 2012.…”
Section: Growth and Developmentmentioning
confidence: 99%
“…These authors observed that above this concentration level, growth is negatively affected due to disruption of plant metabolism, with a subsequent reduction in growth. Bazihizina et al (2012) evaluated the growth of A. nummularia under 10 mM, 120 mM, 230 mM, 450 mM and 670 mM of NaCl and observed, 21 days later, an increase in growth at the interval of 120-230 mm of NaCl. However, at 450 mM, growth was similar to that of plants exposed to 10 mM of NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…For the levels of 450 mM and 600 mM, this increase was linear (p < 0.01), whereas, for the levels of 150 mM and 300 mM, effects of the time under salt stress imposition were quadratic (p < 0.01). Mean values obtained at 45 days for the (Hassine et al 2008, Bazihizina et al 2009). …”
Section: Resultsmentioning
confidence: 99%